Massive Blood Transfusion in Patients with Ruptured Abdominal Aortic Aneurysm. Issue 5 (November 2016) - Montan, C.; Hammar, U.; Wikman, A.; Berlin, E.; Malmstedt, J.; Holst, J.; Wahlgren, C.M.
Abstract : Objectives: The aim was to study blood transfusions and blood product ratios in massively transfused patients treated for ruptured abdominal aortic aneurysms (rAAAs). Methods: This was a registry based cohort study of rAAA patients repaired at three major vascular centres between 2008 and 2013. Data were collected from the Swedish Vascular Registry, hospitals medical records, and local transfusion registries. The transfusion data were analysed for the first 24 h of treatment. Massive transfusion (MT) was defined as 4 or more units of red blood cell (RBC) transfused within 1 h, or 10 or more RBC units within 24 h. Logistic regression was used to calculate the odds ratio of 30 day mortality associated with the ratios of blood products and timing of first units of platelets (PLTs) and fresh frozen plasma (FFP) transfused. Results: Three hundred sixty nine rAAA patients were included: 80% men; 173 endovascular aneurysm repairs (EVARs) and 196 open repairs (ORs) with median RBC transfusion 8 units (Q1–Q3, 4–14) and 14 units (Q1–Q3, 8–28), respectively. A total of 261 (71%) patients required MT. EVAR patients with MT ( n = 96) required less transfusion than OR patients ( n = 165): median RBC 10 units (Q1–Q3, 6–16.5) vs. 15 units (Q1–Q3, 9–26) ( p = .002), FFP 6 units (Q1–Q3, 2–14.5) vs. 13 units (Q1–Q3, 7–24) ( p < .001), and PLT 0 units (Q1–Q3, 0–2) vs. 2 units (Q1–Q3, 0–4) ( p = .01). Median blood product ratios in MT patients were FFP/RBC (EVAR group 0.59 [0.33–0.86], OR group 0.84 [0.67–1.2]; p < .001], and PLT/RBC (EVAR 0 [0–0.17], OR 0.12 (0–0.18); p < .001]. In patients repaired by OR a FFP/RBC ratio close to 1 was associated with reduced 30 day mortality ( p = .003). The median PLT/RBC ratio was higher during the later part of the study period ( p < .001, median test), whereas there was no significant difference in median FFP/RBC ratio ( p = .101, median test). Conclusion: The majority of rAAA patients undergoing EVAR required MT. EVAR patients treated with MT had lower FFP/RBC and PLT/RBC ratios than OR patients with MT. The mortality risk was lower with FFP/RBC ratio close to 1:1 in open repaired patients requiring MT. The 24 h PLT/RBC ratio increased over the study period.